Hands-on or Gloved Approach? Unveiling Patient Experiences in Orthopaedic Foot and Ankle Clinics - Yvonne C. Conway MD; Andrea B. Rincon BS; Samuel Simister MD; Frank Sierra BS; Christopher D. Kreulen MD; Eric Giza MD (Foot & Ankle Orthopaedics)
Category: Other Introduction/Purpose: Current literature suggests that patients feel medical exam gloves are often overused or used inappropriately, while also having concerns about the possibility of cross-contamination with glove utilization. Additionally, there is very little research on the effect that glove use has on patient’s perceptions of physical exam quality and surgeon personability. The purpose of this research project is to determine whether patients that are having their foot and ankle examined prefer their orthopaedic surgeon to wear medical exam gloves. Methods: Anonymous surveys were administered and collected during clinic for two different fellowship trained foot and ankle orthopaedic surgeons at a single institution. Any patient willing to sign a consent form was included. Patient age, gender, and reason for visit were collected along with a survey of 5 questions on glove utilization. Survey questions were scored on a Likert scale, with 1=strongly agree, 2=agree, 3=neutral, 4=disagree, and 5=strongly disagree. Descriptive statistics, data normalcy, and appropriate significance tests were used to analyze results while controlling for glove utilization (yes or no), gender (female or male), and age group (< 39, 40-49, 50-59, 60-69, and 70+), at p< 0.05 significance. Results: In total, 99 patients agreed to complete the survey (53.5% female and 36.4% male, with a mean age of 55.3 and 54.8, respectively). Overall, physicians used gloves more with male than female patients (33.3 vs 9.43%, p =0.059), although males were slightly more agreeable to preferring no gloves (2.86 vs. 3.17). When the physician wore gloves, patients were more agreeable to glove use for themselves (2.5 vs. 3.24, p=0.001) and for others (2.21 vs. 3.0, p< 0.001). Patients across all groups were agreeable with glove use when examining wounds (range 1.74–2.47.) For all patients, gender, glove use, and age had no effect on agreeing that their physical exam was thorough (average 1.61±0.726) and on disagreeing that gloves effected provider demeanor (average 3.32±0.874). Conclusion: In general, glove use by foot and ankle orthopaedic surgeons did not negatively impact patient perception of physical examination thoroughness, nor did it confer less personability onto their physician. While patients across all groups demonstrated a slight preference for glove use during wound examinations, glove use preference in general was otherwise neutral. These results suggest that, on average, the utilization of gloves does not impact patient care and may therefore be up to the discretion of the provider.